Representing ecological threats and negotiating green built environment - Kerr, Thor Antony (Curtin University, 2012)
Amid a prevalence of textual references about human-induced ecological threats in contemporary society, several studies have investigated the discursive production of such threats and their solutions by policy-making institutions. Yet, this focus on institutional discourse has suggested a less comprehensive analysis of how ecological threats are represented by engaged citizens attempting to influence environmental policy through truth-producing public conversation. Out of this context, this thesis was devised to investigate ecological threat representation in relation to social negotiation of meanings of green built environment. Specifically, it was designed to answer the question of how representation of ecological threats affects the meaning of green built environment and the practices through which this meaning is produced.Answering this question required a method of investigating the positioning, disruption, stabilization and mutual functionalization of ecological threats and proposed solutions in urban planning discourse. Theoretical insights from cultural studies, critical theory, psychoanalysis, geography and media studies were incorporated into a method of analysing various types of public and media texts about ecological threats and a proposed green built environment – North Port Quay, in Fremantle, Western Australia.The analysis found that an apparently universal global ecological threat, such as climate change, was read in heterogeneous ways; and these readings were particularly influenced by sensual experience of environmental objects. It also found that production of meaning of green built environment depended upon a subject reading solutions into an environmental narrative that mutually functionalized with any significant ecological threats read into the narrative. It found that spatially and temporally immediate threats were more meaningful and motivating than distant, future threats; and that people responded conservatively when they realized that a sensually experienced object of the environment faced immediate threat.These findings have implications for understanding the relations of imposing and resisting green zones of capital accumulation, and for understanding the separation of analysis from action in liberal democracy. The findings suggest a way out of ecological crisis through an ethics of ecological threat representation that acknowledges the operation of affective investment in practical reason. This thesis is expected to make an interdisciplinary contribution, encouraging dialogue between urban planning theory and cultural studies as well as between critical theory and studies on sustainability. It should also further understandings of the complex negotiations of both ecological threats and green built environments.